Characterization of an Automated Spinning‐Band Column as a Module for Laboratory Distillation. Issue 9 (3rd August 2021) - Bittorf, Lukas; Böttger, Nils; Neumann, Daniel; Winter, Alina; Kockmann, Norbert
Abstract: Modularization is a promising technology to respond to short product life cycles. Not only in production but also in the laboratory, the concept of modularization can help to quickly explore new products or processes. A modular continuously operated spinning‐band distillation column for small product amounts is presented and characterized regarding operating window and separation efficiency. The column can be used either for first product amounts within a small‐scale production or as feasibility studies for distillation in a scale‐up context with small amounts of resources, energy, and time. By introducing the modular automation concept and a certain degree of automation structures, this column can be operated almost fully automatically and integrated quickly to higher automation structures such as a process orchestration layer. Abstract : A modular continuously operated spinning‐band distillation column for small product amounts is presented and characterized regarding operating window and separation efficiency. The proposed column can be applied either for first product amounts within a small‐scale production or as feasibility studies for distillation in a scale‐up context with small amounts of resources, energy, and time.